In vivo confocal microscopic study of cornea verticillata and limbus deposits in patients with Fabry disease - Zhou, Xuecong; Zhao, Yawen; Li, Yingsi; Yuan, Yujing; Yan, Xiaoming; Zhang, Wei; Wu, Yuan (Frontiers in Medicine, 2025)
PurposeThis study was aimed to investigate the microstructure characteristics of cornea verticillata and limbus deposits in patients with Fabry disease (FD) using in vivo confocal microscopy (IVCM).MethodsA total of 60 eyes from 30 patients diagnosed with FD were examined and compared with 36 eyes from 18 healthy controls in this prospective, cross-sectional, controlled, single-center study. The initial assessment of cornea verticillata (CV) was conducted using slit-lamp microscopy. Subsequently, IVCM was performed to assess deposits in the corneal and limbal epithelium. We compared the differences between the sexes (heterozygous and hemizygous) and phenotypes (classical and non-classical).ResultsThe epithelial deposit detection rate with IVCM was statistically higher (52/60, 86.67%) compared to the biomicroscopic evaluation of CV using a silt lamp (46/60, 76.67%) (p = 0.031). A higher prevalence of corneal epithelial deposits was observed in the classical phenotype as compared to the non-classical phenotype (p = 0.023). Surprisingly, cardiac variants previously lacking cornea verticillata show a high prevalence (85.71%) of corneal epithelial deposits under IVCM. The prevalence and severity of deposits, especially in limbal epithelial rete pegs, were higher in FD than in controls (p < 0.001).ConclusionCompared with slit-lamp microscopy, IVCM provides a more effective tool for examining the epithelial deposits in patients with FD. Patients with FD demonstrated a profound bilateral increase in corneal epithelial deposits and limbal hyperreflective cells compared to controls, with more prominent pathological changes observed in classical phenotype individuals. The high prevalence of epithelial deposits observed through IVCM in the cardiac variant highlights the essential ability of IVCM as an effective diagnostic tool.